PENGARUH LENDIR BEKICOT TERHADAP NYERI PADA TIKUS PUTIH - Lutfi Hendra Kusuma (FKU 12 UMY, 2011)
Snails are hermaphrodite animals which are found in damp places and gastropods belonging to the class that are active during the day. Snails are also often used in traditional medicine, because the extract of snail meat and mucus is very useful for treating various diseases such as abortion, pain during menstruation, inflammation of the lining of the eye, tooth pain, itching, heart and others. The aims of research is determine the effect of snail slime can reduce pain in the rat and whether ther